Administration of a soluble ADPase, AZD3366, on top of ticagrelor confers additional cardioprotective benefits to that of ticagrelor alone. (25th November 2020) - Vilahur, G; Arzanauskaite, M; Sutelman, P; Ben-Aicha, S; Gutierrez, M; Casani, L; Fjellstrom, O; Carlsson, L; Hidalgo, A; Badimon, L
Abstract: Background: Preclinical and pilot human studies suggest platelet-independent cardioprotective effects of ticagrelor most likely due to its ability to block cellular uptake of adenosine. Adenosine is a potent endogenous protective molecule, concentrations of which locally rise as a response to ischemia because of the breakdown of extracellular ATP by an endothelial ADPase (apyrase, CD39) to AMP that is subsequently converted to adenosine by CD73. Purpose: In the present study we used cardiac magnetic resonance (CMR) imaging in a pig model of myocardial infarction (MI) to examine whether administration of a recombinant soluble form of ADPase, AZD3366 (APT102), confers additional benefits to that of ticagrelor alone in terms of reduced infarct size and improved heart function. Methods: Pigs (n=20) were administered an oral loading dose of ticagrelor (180mg) and 2h later subjected to MI induction (1.5h closed-chest LAD coronary balloon occlusion). Prior to reperfusion, pigs were randomized to intravenously receive 1) vehicle (n=5); 2) 1mg/kg AZD3366 (n=5); or 3) 3mg/kg AZD3366 (n=5). After reperfusion all pigs were administered ticagrelor (90mg/bid) for 42 days. A non-treated control-MI group (n=5) was run for comparative purposes. Serial-CMR imaging was performed at baseline and 3 and 42 days post-MI for global and regional structural and functional assessments. Light transmittance aggregometry (LTA; challenged by 5, 10 and 20μM ADP) and ear bleeding time were monitored throughout the study. Results: Ticagrelor significantly reduced edema formation (29.8±1.9 vs. 13.1±0.9%LV) and limited infarct size (17.7±1.5 vs. 8.2±1.2%LV) at 3 days post-MI as compared to control-MI pigs (p<0.05), an effect that persisted up to 42 days. Infusion of 1mg/kg AZD3366 showed a clear signal towards further prevention of myocardial damage that reached significance at doses of 3mg/kg (additional reduction of 35% and 52% in edema and infarct size, respectively, as compared to pigs treated with ticagrelor alone; p<0.05). Left ventricular ejection fraction was higher in all ticagrelor-treated pigs at 3 and 42 days post-MI vs. control (p<0.05). Yet, regional analysis of the jeopardized myocardium revealed that pigs administered 3mg/kg AZD3366 on top of ticagrelor presented minimal dysfunctional segmental contraction as compared to the mild hypokinetic and akinetic disturbances observed in ticagrelor-alone and control-MI pigs (χ 2 p<0.05 vs. all). Ticagrelor inhibited ADP-induced platelet aggregation by 30% and addition of AZD3366 acutely abolished (90% inhibition) LTA at all tested ADP doses, an effect remaining significant up to 3 days post-infusion. Ear bleeding time was not affected by AZD3366. Conclusion: Infusion of a soluble recombinant ADPase (AZD3366) on top of ticagrelor leads to a greater cardioprotection as compared to ticagrelor alone. Co-administration of both drugs in AMI patients undergoing revascularization deserves to be investigated. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Ministerio de Ciencia, Innovaciόn y Universidades / Instituto de Salud Carlos III